Teaching Antimicrobial Stewardship to Infectious Disease Fellows Through Simulated Interdisciplinary Scenarios - Alice E. Barsoumian; Brian K White; Heather C. Yun (Association of American Medical Colleges, 2018)
Introduction While several approaches have been described to teach antimicrobial stewardship (AS) practices, fewer have been aimed at infectious disease physicians. We developed a series of simulated AS meetings to train infectious disease fellows in the synthesis of AS interventions. Methods Three simulated AS committee scenarios were developed. Background lectures were given 1 week prior to the simulation during which multidisciplinary roles were assigned. Precourse work included review of primary literature pertinent to the scenario. Simulations were conducted over 1.5 hours. Individual and team performances were evaluated. Pre- and postsurveys were collected from fellows and faculty members to assess the format. Results Six infectious disease fellows participated in the series. Fellows demonstrated information synthesis and improvements in individual and team performance. Eighty-three percent of fellows before the simulation series and 100% postseries reported educating others on AS principles in the previous month. Fellows were satisfied with the series and requested more scenarios. Eight faculty members completed surveys. Thirty-eight percent of faculty before the series and 63% after completion reported that fellows viewed antimicrobial preauthorization as useful or necessary. Faculty supported the format, found it useful in evaluation of learners, and perceived that fellows benefited from the approach. Discussion Simulation is an effective and enjoyable way to train infectious disease fellows in AS and team utilization. Fellows demonstrated improvement in AS knowledge, skills, and attitudes and developed evidence-based interdisciplinary plans to solve AS challenges. Faculty also viewed this strategy as effective and sustainable.